Cyborg Enhancements: Sergius Bulgakov and His Sophiological Perspective - Sisto, Walter N. (Irish theological quarterly, 2023)
Although Bulgakov did not write about cyborg ethics, his thesis that humankind is the hypostasis of the creaturely Sophia provides a dynamic framework to assess the morality of technological alterations to the human body. As the hypostasis of the creaturely Sophia, the human person has limitless possibilities, including miracle-working. And thus, Jesus Christ’s miracles reflect capacities that God intends for all human persons, with the greatest miracle being the resurrection of the body. Bulgakov’s thought on miracles offers both a defense of cybernetic modifications and a norm for their limits. This article resources Bulgakov’s sophiology to provide an Eastern Christian perspective on cybernetic enhancement technologies. It also engages Bulgakov’s sophiology with current scholarship on cybernetic enhancement technologies.